Immunization of mice with a recombinant adenovirus vaccine inhibits the early growth of Mycobacterium tuberculosis after infection. - Edward O Ronan; Lian Ni Lee; Peter C L Beverley; Elma Z Tchilian (PLoS ONE)
Background In pulmonary Mycobacterium tuberculosis (Mtb) infection, immune responses are delayed compared to other respiratory infections, so that antigen-specific cells are not detected in the lungs earlier than day 14. Even after parenteral immunization with Bacille Calmette Guerin (BCG) or a subunit vaccine, the immune response after Mtb challenge is only slightly accelerated and the kinetics of pulmonary Mtb growth do not differ between naïve and immunized animals up to day 14. Methods and findings Mice were immunized intranasally with a recombinant adenovirus expressing mycobacterial antigen 85A (Ad85A), challenged by aerosol with Mtb and the kinetics of Mtb growth in the lungs measured. Intranasal immunization with Ad85A inhibits Mtb growth in the early phase of infection, up to day 8. Protection is sustained for at least 7 months and correlates with the presence of antigen-specific activated effector CD8 T cells in the lungs. Antigen 85A-specific T cells respond to antigen presenting cells from the lungs of mice immunized with Ad85A 23 weeks previously, demonstrating the persistence of antigen in the lungs. Conclusions/significance Intranasal immunization with Ad85A can inhibit early growth of Mtb because it establishes a lung antigen depot and maintains an activated lung-resident lymphocyte population. We propose that an optimal immunization strategy for tuberculosis should aim to induce both lung and systemic immunity, targeting the early and late phases of Mtb growth.